Progression of Disease and Viral Agents in Infants Hospitalized for Lower Respiratory Tract Infections - Ayşe Banu Esen; Meltem Erol; Didem Kafadar; Özlem Bostan Gayret; Özgül Yiğit; Tuğçe Damla Dilek; Kübra Yılmaz (Galenos Yayinevi, 2019)
Aim:Acute viral respiratory tract infection is the leading cause of hospitalization for infants and young children in developed countries and is a major cause of death in developing countries. The aim of this study was to identify the viruses in children hospitalized for lower respiratory tract infections (LRTI) during the winter period and to evaluate the relationship between the clinical features of these patients and the severity of their disease.Materials and Methods:The nasopharyngeal aspirates of 200 patients aged 0-24 months hospitalized with a diagnosis of LRTI were analyzed using the real-time polymerase chain reaction method. We looked for associations between the viral agent, duration of hospitalization and respiratory distress scale.Results:The viral factor was identified in 150 (75%) patients. Rhinovirus was the most frequent viral agent followed by respiratory syncytial virus and adenovirus; (52.67%), (16.0%) and (8.67%) respectively. The average length of hospitalization for respiratory syncytial virus (p=0.001), adenovirus (p=0.009), influenza A virus (p=0.007), and bocavirus (p=0.009) infections were significantly longer. Adenovirus (p=0.029), respiratory syncytial virus (p=0.001) and bocavirus (p=0.009) were significantly associated with length of hospitalization. No significant correlation was identified between the viruses and respiratory distress scores (p>0.05).Conclusion:We conclude that in hospitalized children with LRTIs, rhinovirus was the most frequently observed viral etiological agent. A longer period of hospitalization was needed for respiratory syncytial virus, adenovirus and bocavirus in infants with LRTIs. Infants with respiratory infections should be monitored due to the risk of developing severe complications during disease progression.